Field Testing of Moving Short‐baseline Navigation for Autonomous Underwater Vehicles using Synchronized Acoustic Messaging. Issue 4 (8th May 2013) - Wolbrecht, Eric; Anderson, Michael; Canning, John; Edwards, Dean; Frenzel, Jim; Odell, Doug; Bean, Tom; Stringfield, Jordan; Feusi, J.; Armstrong, B.; Folk, A.; Crosbie, B.
<x xml:space="preserve">Abstract</x> This paper presents the results from field testing of a unique approach to the navigation of a fleet of autonomous underwater vehicles (AUVs) using only onboard sensors and information provided by a moving surface ship. The approach, considered moving short‐baseline (MSBL) navigation, uses two transponders mounted on a single surface ship that alternately broadcast acoustic messages containing one of the parameters of the kinematic state of the surface ship. The broadcasts are initiated according to a predefined schedule so that the one‐way travel time (OWTT) of the acoustic messages may be used to determine the range to the transponder. Each AUV in the fleet uses the surface ship state measurements and ranges provided by the acoustic messages in two extended Kalman filters (EKFs) for state estimation. The first EKF merges the intermittent surface ship state measurements with a kinematic model to estimate the state of the surface ship. This is necessary because the presented approach uses 13‐bit acoustic messages as opposed to the more commonly used 32‐byte messages, which allow the full state to be encoded in a single broadcast. The second EKF uses the current surface ship state estimate to properly interpret the acoustic ranges, combining them with a kinematic model to estimate the state of the AUV itself. Numerous MSBL navigation experiments were compared against a more traditional approach using a long‐baseline (LBL) array of transponders and OWTT acoustic ranging. The results of all tests were verified by independent LBL measures of position.